Molecular and Structural Damage to Escherichia coli Produced by Antibody, Complement, and Lysozyme Systems - Wilson, Lawrence A. (1968)
The antibacterial action of antibody (normal and hyperimmune), complement, and lysozyme has been studied by correlating the ultrastructural and biochemical changes that they cause in smooth Escherichia coli. Both normal and hyperimmune antibody, in the absence of lysozyme, produced complement-dependent release, into the suspending medium, of 63 to 72% of the (32)P-labeled phospholipid and 74 to 85% of the small molecular bacterial constituents. Macromolecular nucleic acid labeled with (32)P was not released. By phase microscopy, these cells appeared as bacilli but their ultrastructure showed general swelling, with smoothing of the normally wrinkled outer cell wall layers. Cytoplasmic membranes were damaged and the internal cell structure was disorganized. Membranous spherules, apparently from the outermost putatively lipopolysaccharide cell layer, were released into the medium. When lysozyme was added to antibody and complement, (32)P-labeled macromolecular constituents were released from the cells. Damage to ultrastructure then included loss of cell wall rigidity, cell wall breakage, and some spheroplast formation. Characteristic fibrillar fragmentation was seen in cell wall mucopeptide layers. The relationships between antibody-complement dependent release of bacterial phospholipid, loss of selective cell permeability, and increase in sensitivity to lysozyme are discussed.